Zvezda Shipyard Project: Global Implications and Its Influence on the Russian Economy - I. I. Sechin (Vestnik MGIMO-Universiteta)
This article expands upon the author's previous work regarding the Vostok Oil project, initially discussed in the Gubkin University journal. It focuses on the establishment and development of the Zvezda Shipyard project, arguing its critical role in the potential development of the Vostok Oil and Gas province. The paper posits that without the Zvezda Shipyard, it would not be feasible to exploit the Vostok Oil and Gas province or significantly enhance the transportation and logistics capabilities of the Northern Sea Route (NSR). The development of Zvezda's new production facilities is presented as essential for the advancement of the Russian Arctic, facilitating a pivotal eastward shift in the Russian economy. The significance of the Zvezda project and the strategic decisions leading up to it are discussed in detail, demonstrating how they integrate the development of the NSR, the exploitation of Vostok Oil fields, and the establishment of investment and technological foundations for Russia's long-term strategy. This strategy addresses both socio-economic goals and defense and security challenges. Additionally, the paper provides quantitative analyses of the multiplicative effects generated by the Zvezda Shipyard project's realization.